School's first day of school - Rex, Adam; Robinson, Christian (New York : A Neal Porter Book, Roaring Brook Press, 2016)
It's the first day of school at Frederick Douglass Elementary and everyone's just a little bit nervous, especially the school itself. What will the children do once they come? Will they like the school? Will they be nice to him? The school has a rough start, but as the day goes on, he soon recovers when he sees that he's not the only one going through first-day jitters.
Ages 4-8.
Preschool
2017 Texas 2x2 List.
Charlotte Zolotow Award Nominee, 2017
Keywords: First day of school -- Juvenile fiction; Elementary schools -- Juvenile fiction; School buildings -- Juvenile fiction; Worry in children -- Juvenile fiction; First day of school -- Fiction; Schools -- Fiction; School buildings -- Fiction; Buildings -- Fiction; First day of school -- Fiction; JUVENILE FICTION / Social Issues / New Experience; Picture books for children